About the Sailors of History: The African Duarte José Martins da Costa and the Atlantic Slave Trade “Petty Network” (Rio de Janeiro – Angola – Recife – Benin, 19th Century) - Costa, Valéria (2022)
This article presents fragments of the life of Duarte José Martins da Costa, a sailor whose experiences of enslavement and freedom were at the crossroads of the slave trade between West and Central-West Africa and Brazil. Through his trajectory, we examine the Atlantic connections between small businesses, seafarers, captive brokers; freed, enslaved, and free people; Europeans, Americans, Africans; whites, blacks, and “mixed race” people who constituted what we call the “small network” of the slave trade and who were also responsible for its breadth illegal in nineteenth-century Brazil.